1985
DOI: 10.1177/0148607185009005590
|View full text |Cite
|
Sign up to set email alerts
|

VA Cooperative Study on Alcoholic Hepatitis III: Changes in Protein‐Calorie Malnutrition Associated with 30 Days of Hospitalization with and without Enteral Nutritional Therapy

Abstract: Patients with moderate to severe alcoholic hepatitis and features of protein-calorie malnutrition were studied with respect to changes in their nutritional status during 30 days of hospitalization. Thirty-four patients served as controls, were given a 2500 kcal hospital diet and allowed to eat ad libitum. Twenty-three patients were given, in addition to the hospital diet, a nutrition supplement high in calories, protein, and branched-chain amino acids (Hepatic Aid). Because of anorexia, the controls consumed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…This finding is in agreement with that observed in a randomized controlled trial of 30-day enteral feeding versus conventional diet in AH, in which all deaths in the enteral feeding group were concentrated in the first week of therapy. 11 Other characteristics of the enteral diet used in the present trial (Table 1) might also contribute to its therapeutic effect. It was a low-fat diet (about 15% of energy as fat), and medium-chain triglycerides and oleic acid accounted for most of its lipid content.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is in agreement with that observed in a randomized controlled trial of 30-day enteral feeding versus conventional diet in AH, in which all deaths in the enteral feeding group were concentrated in the first week of therapy. 11 Other characteristics of the enteral diet used in the present trial (Table 1) might also contribute to its therapeutic effect. It was a low-fat diet (about 15% of energy as fat), and medium-chain triglycerides and oleic acid accounted for most of its lipid content.…”
Section: Discussionmentioning
confidence: 98%
“…Protein-energy malnutrition has been shown to worsen the prognosis of alcoholic hepatitis [32]. One large controlled trial has shown benefits of short-term enteral feeding in patients with alcoholic hepatitis, including improved liver function tests and shorter hospital stay [33]; however, no decrease in mortality has been reported. During the anorectic phase of alcoholic hepatitis, enteral nutrition should be started to provide sufficient protein and energy to support these catabolic patients.…”
Section: Alcoholic Hepatitismentioning
confidence: 99%
“…Short-term mortality and one-year probability of survival between groups were similar, but a significantly better outcome during the one-year follow-up was recorded for patients treated with TEN compared to those treated with prednisolone alone (2 vs. 10 deaths, respectively; p ¼ 0.04), mostly due to infections. Two other trials showed a treatment benefit on surrogate parameters of nutritional status such as serum albumin, retinol-binding protein and nitrogen balance [58,59], but not on survival.…”
Section: Nutritional Therapymentioning
confidence: 99%
“…Though not being an independent prognostic factor for survival, malnutrition correlates significantly with liver dysfunction in ASH [56]. So far, five trials have studied the efficacy of oral or enteral nutritional support in patients with ASH [55,[57][58][59][60][61].…”
Section: Nutritional Therapymentioning
confidence: 99%